Hubungan pengetahuan dan sikap terhadap hygiene sanitasi petugas penjamah makanan di warung makan - Santri Pertiwi; Nadiya Turrahmi (Journal of Health and Therapy, 2024)
Food sanitation supervision starts with six sanitation principles, from selecting food ingredients to serving, to protect food from hazards caused by poor processing and storage. Many restaurants with food handlers who do not meet food sanitation requirements can lead to foodborne disease outbreaks. The research method used is a descriptive-analytic, cross-sectional design, with a Chi-Square statistical test. This research was conducted in Woyla District, West Aceh Regency, in August 2022. The research technique used was total sampling, with a population of 30 restaurants and a sample of 30 restaurants. The research results showed that knowledge and attitude were not significantly related to hygiene and sanitation among food handlers in restaurants in Woyla District, West Aceh Regency, in 2022. It is recommended that restaurant owners be actively involved and responsible for improving the hygiene and sanitation of food handlers in their restaurants.